PROFITABILITAS, UKURAN PERUSAHAAN, DAN NILAI PERUSAHAAN TERHADAP PRAKTIK PERATAAN LABA - Hermawati Nurciptaning Arum; Mohamad Rafki Nazar; Wiwin Aminah (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2017)
Income smoothing is strategy where management increases or decreases profits to reduce fluctuation. Income smoothing is common form of profit management. Income smoothing measured using Eckel Index which can distinguish between companies that did and did not undertake income smoothing. Eckel uses CV for profit and net income. Index which has a result less than 1 is classified as a grader, index which has a result more than 1 is classified as nongrader. This study aims to determine the effect of profitability, firm size, and value of company on income smoothing. The object using company registered in Jakarta Islamic Index 2011-2015. Sampling technique used in this study is purposive sampling. Analytical method used in this study is logistic regression. The results show that profitability, company size, and value of company simultaneously influence income smoothing. Partially, profitability and company size significantly negative direction of income smoothing, the value of the company have significant influence with a positive direction toward the practice of income smoothing.